THE END OF THE BEGINNING: VIRGIL'S AENEID IN OVID, AMORES 1.2*. (10th September 2015) - Goh, Ian
Abstract : It is well known that Ovid's Amores begin with a reference to Virgil's Aeneid in the very first word, arma ('weapons', Am. 1.1.1 = Verg. Aen. 1.1), which implies that the elegist had been composing epic before Cupid, by stealing a foot, apparently forced him to write elegy. In spite of this incapacitation at the hands of the love god, Ovid continues to toy with Virgil's epic by making the first two poems of his collection of elegiacs into a mini- Aeneid, or – to be precise – by making the second poem of the collection into the second half of the Aeneid . One result is that the three-book edition of Amores threatens to be over even before it has begun. Another is that Ovid can be identified with the Latin enemies, on the wrong side of history, from the Aeneid . I restrict the argument largely to what can be observed in Amores 1.2, leaving aside, for instance, the possibility that Ovid shot by Cupid's arrow in 1.1 might be thought comparable to Dido, similarly shot and causing Aeneas to dally in Carthage with her in Aeneid 4.